2011
DOI: 10.1039/c1nj20421a
|View full text |Cite
|
Sign up to set email alerts
|

Electrode processes at gas|salt|Pd nanoparticle|glassy carbon electrode contacts: salt effects on the oxidation of formic acid vapor and the oxidation of hydrogen

Abstract: The electrochemical oxidation of formic acid to CO 2 is facile at nano-palladium catalysts. In conventional electrochemical systems this process is conducted in aqueous phase and the resulting formation of poorly soluble CO 2 gas can limit the kinetics. Here, an alternative electrochemical system with the gas phase in closer contact to the palladium nanoparticle catalyst is investigated based on a glassy carbon electrode and a solid salt electrolyte. It is demonstrated that the reaction zone of salt (here (NH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In recent reports the use of salt|electrode contact processes has been demonstrated for the case of salt surface immobilized redox systems, for palladium catalyst coated electrodes, and for textile-coated electrodes . In this study it is demonstrated that ammonium nitrate salt crystals can be used as a “thin film electrolyte phase” also in a nonpolar solvent such as hexane to electrically connect the working electrode and a counter-reference electrode (see Figure B).…”
Section: Introductionmentioning
confidence: 75%
“…In recent reports the use of salt|electrode contact processes has been demonstrated for the case of salt surface immobilized redox systems, for palladium catalyst coated electrodes, and for textile-coated electrodes . In this study it is demonstrated that ammonium nitrate salt crystals can be used as a “thin film electrolyte phase” also in a nonpolar solvent such as hexane to electrically connect the working electrode and a counter-reference electrode (see Figure B).…”
Section: Introductionmentioning
confidence: 75%
“…Recently it has been shown that fast hydrogen gas sensing could be achieved with electrochemical micro-sensors [28,29] or when utilizing a gas-salt-electrode contact triple phase boundary system [30]. A palladium catalyst was immobilized on a glassy carbon electrode surface and placed in contact to solid ammonium sulfate and hydrogen gas.…”
Section: Introductionmentioning
confidence: 99%